Antibacterial activity of ethyl acetate extracts of fungal endophytes isolated from leaf gambir leaves (Uncaria gambir (Hunter) Roxb) - Efendi, M. Rifqi; Rusdi, Mesa Sukmadani; Dinda, Anita (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Gambir (Uncaria gambir (Hunter) Roxb) is a Sumatran medicinal plant that has various bioactivities, including antibacterial. This study aims to isolate endophytic fungi from gambier leaves and test the antibacterial activity of ethyl acetate extracts of fungal endophytes from gambir leaves. The fungal endophytes were isolated by inoculating the fungus obtained from gambir leaves on potato dextrose agar (PDA) media. The fungal endophytes were identified microscopically and macroscopically. Furthermore, the fungal endophytes were cultivated using rice media : aquades (100 : 110). The cultivated fungus was macerated using ethyl acetate solvent and tested using a screening test. The antibacterial activity of the ethyl acetate extract of endophytic fungi was conducted using the agar diffusion method against Gram-positive bacteria (Bacillus subtilis ATCC 6633 and Staphylococcus aureus ATCC 25923) and Gram-negative bacteria (Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853). This study has revealed five fungal isolates from gambir leaves and identified the isolates as Penicillium sp 1 (0.39 g), Penicillium sp 2 (0.26 g), Neopestalotiopsis sp (0.97 g), Colletotrichum capsici (0.46 g), and Aspergillus sp (0.25 g). The ethyl acetate extracts of each fungal endophyte show the presence of phenolic compounds and have inhibition against Gram-positive and Gram-negative bacteria. The highest antibacterial activity is shown by ethyl acetate extracts of the fungal endophytes of Neopestalotiopsis sp at a concentration of 7.5% on P. aeruginosa ATCC 27853 23±3.9 mm and S. aureus ATCC 25923 14±2.5 mm. Tests on B. subtilis ATCC 6633 and E. coli ATCC 25922 with the highest inhibition zones were indicated by the ethyl acetate extracts of the fungus Aspergillus sp of 15.3±4 mm and 14±1.9 mm, respectively.